PELAKSANAAN EVALUASI DAN PENGEMBANGAN KONSEP KURIKULUM PENDIDIKAN ISLAM SEBAGAI RASIONALISASI AKADEMIK DI SEKOLAH MENENGAH ATAS - Ukun, Ukun Kurnia; Arifin, Muhammad Arifin; samudi, samudi (Almarhalah: Jurnal Pendidikan Islam, 2025)
Evaluation of the Islamic education curriculum is an activity to determine the level of progress of students in an educational process that can be used as a reference and indication to revise or develop the Islamic religious education curriculum. While the evaluation results become a reference for the development of the Islamic education curriculum, namely an activity to create an Islamic religious education curriculum through a process that combines one component with another in order to realize a better Islamic religious education curriculum in the future. This study aims to examine and analyze the implementation of evaluation and development of the concept of Islamic education curriculum as an academic rationalization in high school. This research uses a qualitative method of phenomenology type whose unit of analysis is Daar El-Azhar High School. The data collection uses observation and interviews as well as documents, with the analysis of the research data using data reduction, display model and conclusion drawing. The results of the research findings found that the implementation of Islamic education curriculum evaluation in senior high schools has been based on academic rationalization in the form of: formative and summative assessments, supervision of the learning process, peer assessment learning communities and measuring the level of satisfaction with stakeholders. The implementation of Islamic education curriculum development in senior high schools has been based on academic rationalization in the form of: detailed learning modules, diverse teaching material sources, specific Islamic education subjects and extracurricular Islamic education. The Islamic religious education curriculum in senior high schools according to the development results, in the form of; specific teaching modules, taking teaching material sources from package books, reference books, journals, the internet, classical and modern books and specific Islamic religious education subjects, namely; Qur'an hadith and aqidah akhlak and tafsir, fiqh and Islamic history and Arabic.